Effect of dietary protein level on gentamicininduced nephrotoxicity in rats and on the circadian rhythms of food ingestion - Zeeni, Nadine (2006)
All aminoglycosides have the potential to cause nephrotoxicity. Previous studies have shown that this toxicity was altered according to the macronutrient composition of dietary regimens offered to female rats. In a first study, adult female Sprague-Dawley rats adapted to a standard chow diet, the standard chow with 20% added casein or with 55% added casein were treated for 10 days with a nephrotoxic dose of gentamicin sulfate (40 mg/kg/day, i.p.) or a saline solution. Food ingestion patterns and gentamicin nephrotoxicity indices were measured. In a second study, rats were fed the same diets, however, the treatment given was a sham injection. Results suggest that chronic gentamicin treatment leads to a decrease in food intake and flattening of the rhythms of food ingestion. Also, chow feeding and chow added with 20% casein were found to be more protective against gentamicin-induced nephrotoxicity than chow added with 55% casein.